PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING BERBANTUAN MIND MAP PADA SISWA KELAS XI IPA - N.D. Sihombing; N.D. Malau; T. Guswantoro; S.S. Lumbantobing (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2020)
In the process of learning in SMA Budhi Warman 1 Jakarta teachers still tend to use conventional learning centered on the teacher with a sequence of lectures, and question and answer and cause students less active and less creative and cause the still low student learning outcomes. This study aims to determine the effect of learning cooperative learning model with the mind-map media on physics learning outcomes of high school students of Class XI IPA on optical materials. This research was conducted at SMA Budhi Warman 1 Jakarta. The research method used is quasi experimental method with research design is Two Group Pretest-Posttest Design. Class sampling was done randomly (cluster random sampling) research sample amounted to 68 students consisting of 34 students experimental class and 34 students of control class. The research instrument used in this research is the test of learning result. The test of learning outcomes is an objective test of multiple choice questions. Data analysis in research using test-t test obtained that the significance value of 0.00 is smaller than the significance level α = 0.05 (0.00 <0.05). and and from these results the alternative hypothesis (Ha) is accepted. So it can be concluded that there is a significant effect of application of cooperative learning model with mind map and able to improve the learning result of physics. Keywords: Cooperative Learning, Mind Map, Learning Outcomes